2000
DOI: 10.1063/1.372474
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic properties and structures of the Mn-implanted GaAs semiconductor

Abstract: Submicron ferromagnets have been successfully incorporated into semi-insulating (001) GaAs crystals by Mn+ ion implantation and subsequent rapid annealing. Magnetization measurements reveal room-temperature ferromagnetism. The structural and compositional properties of crystallites have been analyzed by transmission electron microscopy, energy dispersion x-ray spectrum, and electron microdiffraction. The results show that crystallites of MnGa and MnAs with a small amount of Ga are formed. Atomic force microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…It was clearly shown that annealing could also promote the formation of Mn-Ga binary phase, which was also confirmed from XRD results of samples with rapid thermal annealing (RTA) at 900 C for 5 min or the work by Chen et al [13].…”
Section: Structural Analysessupporting
confidence: 62%
See 1 more Smart Citation
“…It was clearly shown that annealing could also promote the formation of Mn-Ga binary phase, which was also confirmed from XRD results of samples with rapid thermal annealing (RTA) at 900 C for 5 min or the work by Chen et al [13].…”
Section: Structural Analysessupporting
confidence: 62%
“…On the other hand, ion implantation is also capable of introducing dopant concentrations above the usual equilibrium solid solubility limit. GaN based DMS has been successfully fabricated by implantation [9][10][11] while study on GaAs based DMS by implantation is still too limited after acquiring some results [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The formation of Mn-based nanoclusters in GaAs samples by ion implantation and subsequent annealing [3][4][5] is a relatively simple technique compared to the growth of ͑GaAs͒Mn diluted material by epitaxial techniques, with the advantages of easy control of the Mn relative density and the possibility of spatial confinement with mask patterning. Both GaMn ͑Refs.…”
mentioning
confidence: 99%
“…In addition, ferromagnetic MnAs nanoclusters embedded in GaAs can be created by annealing of GaiMn.As films. (24) In some cases, MnGa•As, phases are observed in addition to the MnGa and MnAs phases (23), indicating that under some conditions it is possible to form ferromagnetic ternary phases. Note that for these GaAs experiments the Mn implants were performed at room temperature, in contrast to our use of elevated substrate temperatures which should reduce the point defect density.…”
Section: Elmentioning
confidence: 99%
“…(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) Both of these phases have Tc values above room temperature (eg. GaMn has Tc's between 450-800 K depending on the amount of Mn in the alloy).…”
Section: Elmentioning
confidence: 99%